Enrichment of Cysteine-Containing Peptide by On-Resin Capturing and Fixed Charge Tag Derivatization for Sensitive ESI-MS Detection - Bąchor, Remigiusz (Molecules, 2020)
High complexity of cell and tissue proteomes limits the investigation of proteomic biomarkers. Therefore, the methods of enrichment of some chemical groups of peptides including thiopeptides are important tools that may facilitate the proteomic analysis by reducing sample complexity and increasing proteome coverage. Here, we present a new method of cysteine-containing tryptic peptide enrichment using commercially available TentaGel R RAM resin modified by the linker containing the maleimide group, allowing thiol conjugation. The captured tryptic peptides containing lysine residue were then tagged by 2,4,6-triphenylpyrylium salt to form 2,4,6-triphenylpyridinium derivatives, which increases the ionization efficiency during mass spectrometry analysis. This makes it possible to conduct an ultrasensitive analysis of the trace amount of compounds. The proposed strategy was successfully applied in the enrichment of model tryptic podocin peptide and podocin tryptic digest.